1985
DOI: 10.1039/f19858100875
|View full text |Cite
|
Sign up to set email alerts
|

Pressure dependence of activation and reaction volumes

Abstract: A simple theoretical model of high-pressure kinetic effects is proposed based on the assumption that characteristic (initial, transition or product) states of a reacting system should be identified with stationary points of an enthalpy surface rather than those of a regular potential-energy surface (p.e.s.). An explicit treatment of the deformation of a p.e.s. promoted by pressure enables one to improve the simple cylinder Stearn-Eyring model of activation volumes so as to describe the pressure dependence of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…[34,35] Second, as a Diels-Alder reaction, the dimerization of cyclopentadiene shows a large pressure effect for which there are experimental data to compare. [11,15,36] In the gas phase, the PES for the dimerization of cyclopentadiene presents three different reaction mechanisms the endo pericyclic reaction, the exo pericyclic reaction, and the stepwise (diradical). The reaction passes through a well-defined transition state to reach the product, without other stationary points along the reaction coordinate.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[34,35] Second, as a Diels-Alder reaction, the dimerization of cyclopentadiene shows a large pressure effect for which there are experimental data to compare. [11,15,36] In the gas phase, the PES for the dimerization of cyclopentadiene presents three different reaction mechanisms the endo pericyclic reaction, the exo pericyclic reaction, and the stepwise (diradical). The reaction passes through a well-defined transition state to reach the product, without other stationary points along the reaction coordinate.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…We close with a historical remark. The development of modeling the pressure effect on chemical reactions began with a seminal paper by Stearn and Eyring [48] in the 1940s, and it has been followed by decisive contributions by Nakahara (1983), [49] Basilevsky (1985Basilevsky ( -1995, [11,12,19] Kl€ arner (1994), [50] Weinberg (2012-2014), [14,15] and Hoffmann (2011). [51] It is a pleasure to recognize that our PCM-XP model has been deeply inspired by all these contributions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We are used to thinking in terms of thermal activation, and we have become skilled at analyzing Arrhenius behaviors to estimate activation energies. Activation volumes may also be significant and can be derived from supercritical high‐pressure measurements . It has been suggested that SCFs jam themselves into interlayer spaces to initiate exfoliation.…”
Section: Summary and Perspective Of Future Developmentsmentioning
confidence: 99%
“…5,6 Although GES are more appropriate for discussion of high pressure effects on condensed phase reaction kinetics and mechanisms, high pressure PES (or, more precisely, enthalpy surfaces) offer a significantly cheaper alternative at sufficiently high levels of compression, when entropy effects are no longer essential. 7 It has previously been demonstrated for the Diels-Alder dimerization of cyclopentadiene 8 and hydrogen transfer between halogen atoms 5 that under the extreme pressure conditions their energy landscapes undergo significant changes resulting in considerable reduction and, sometimes, complete elimination of reaction barriers. In the present work, we discuss general trends in pressure-induced changes to PES of compressed species, and report our findings for hydrogen transfer in hydrocarbon systems and methyl transfer in S N 2 processes in comparison with the results for simple triatomic X-H-Y systems (X,Y= F,Cl,Br).…”
Section: Introductionmentioning
confidence: 99%